C₂m₂(t-t₂)+c₁m₁(t-t₁)=0 t=c₁m₁t₁+c₂m₂t₂/c₂m₂+c₁m₁ объясните почему именно так выразили t

Fajeh Fajeh    1   27.09.2019 01:40    3

Ответы
cuprinainna cuprinainna  08.10.2020 21:36
Решение во вложении.
C₂m₂(t-t₂)+c₁m₁(t-t₁)=0 t=c₁m₁t₁+c₂m₂t₂/c₂m₂+c₁m₁ объясните почему именно так выразили t
ПОКАЗАТЬ ОТВЕТЫ
Kettiplay Kettiplay  08.10.2020 21:36

c₂m₂·(t - t₂)+c₁m₁·(t - t₁) = 0

c₂m₂t - c₂m₂t₂ + c₁m₁t - c₁m₁t₁ = 0

c₁m₁t + c₂m₂t = c₁m₁t₁ + c₂m₂t₂

t·(c₁m₁ + c₂m₂) = c₁m₁t₁ + c₂m₂t₂

t = c₁m₁t₁+c₂m₂t₂ / c₁m₁+c₂m₂

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Физика